Effects of Acupuncture Combined with Biofeedback Therapy on Limb Motor Rehabilitation in Patients with Acute Stroke: Systematic Review and Meta-Analysis. (5th July 2022) - Song, Xinrong; Zhang, Xiaoge; Weng, Yan; Liu, Yu; Shan, Qi; Chen, Wenna; Ma, Wanwan; Dong, Qi; Qu, Dandan; Guo, Yibo; Xiong, Jie; Deng, Fuhua; et al.
Abstract : Objective . The purpose of the systematic review is to verify the effect of biofeedback therapy on limb motor rehabilitation in patients with acute stroke and to provide evidence-based medicine for the promotion and use of biofeedback therapy. Methods . The randomized controlled trials (RCT) of biofeedback therapy in the treatment of cerebral palsy were searched in PubMed, EMBASE, ScienceDirect, Cochrane Library, China National Knowledge Infrastructure (CNKI), China VIP Database, Wanfang Database, and Chinese Biomedical Literature Database (CBM). The starting time and ending time of this study are from the time of building the database of the number of pieces to October 31, 2018. The data included in this study were extracted by two independent researchers and evaluated the bias risk of all the literature included in the study according to the Cochrane manual 5.1.0 criteria. RevMan5.4 statistical software was used to analyze the collected data by meta. Results . This systematic review included 9 RCT studies with a total of 1410 patients. The results of meta-analysis showed that there were significant differences in the improvement of lower limb muscle tension, comprehensive spasm scale score, EMG score, and passive range of motion of ankle joint between biofeedback therapy and routine rehabilitation therapy. Conclusion . Biofeedback therapy can improve lower limb muscle tension, spasticity, EMG integral value, and passive range of motion of ankle joint in children with cerebral palsy and provide better conditions for improving the motor ability of lower extremities in children with cerebral palsy. However, more studies and follow-up with higher methodological quality and longer intervention time are needed to further verify.